ANALISIS PENGARUH PROMOSI MEDIA SOSIAL INSTAGRAM DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA CAFE JENLESS COFFEE & BREAD - Husna, Nurul; Sadli, Andi Muhammad; Nurfai (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2024)
This research is about the influence of Instagram social media promotion and service quality on purchasing decisions at Cafe Jenless Coffee & Bread. The number of samples obtained in this research was 75 customers from various groups for one month, namely primary data obtained in December 2023, processed with the help of the Eviews program using the multiple regression analysis method Y= 0.210+0.267x1 +0.709x2 in this research also uses descriptive statistical data analysis techniques. The results of this research show that Instagram Social Media Promotion and Service Quality have a positive influence on Purchasing Decisions by obtaining R square R2 regression analysis results of 0.729 or 72.9%. This means 72.9%, meaning that together the variables Instagram Social Media Promotion and Quality Service influences the Purchase Decision variable, while the remaining 0.271 or 27.1% is influenced by other factors not included in this research.